Wheat Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2006)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_2006_10
Keywords: MF914; Economics; Crops; MF